2009
DOI: 10.1155/2009/380967
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin Period 3 Is Essential for Enhancement of Isometric Tension in Thin Filament-Reconstituted Bovine Myocardium

Abstract: Tropomyosin (Tm) consists of 7 quasiequivalent repeats known as “periods,” and its specific function may be associated with these periods. To test the hypothesis that either period 2 or 3 promotes force generation by inducing a positive allosteric effect on actin, we reconstituted the thin filament with mutant Tm in which either period 2 (Δ2Tm) or period 3 (Δ3Tm) was deleted. We then studied: isometric tension, stiffness, 6 kinetic constants, and the pCa-tension relationship. N-terminal acetylation of Tm did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 71 publications
8
24
0
Order By: Relevance
“…Our results also show that specific residues of Tm are involved in regulation, because mutation of residues in P2-2-EKD and P3-1-EE mutants did not affect motility. The results agree with previous studies reporting that deletion of P3-P6 had an inhibitory effect on actomyosin (18,19) and that P3 was important for the cooperative activation of the actin filament (20,21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results also show that specific residues of Tm are involved in regulation, because mutation of residues in P2-2-EKD and P3-1-EE mutants did not affect motility. The results agree with previous studies reporting that deletion of P3-P6 had an inhibitory effect on actomyosin (18,19) and that P3 was important for the cooperative activation of the actin filament (20,21).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that individual periodic repeats of Tm had varying degrees of effect on thin filament regulation, indicating that specific regions of Tm contribute differently to its regulatory function (18)(19)(20)(21). EM and 3D reconstruction of actin-Tm filaments with different Tm isoforms have shown that in the absence of Tn and myosin, Tm occupies the blocked or closed position on the actin filament, depending on the Tm and actin isoform (22).…”
mentioning
confidence: 99%
“…6). The results underscore previous reports of particular contributions of each period to actin affinity and thin filament function (11)(12)(13)(14)(15). The relatively minor involvement of hydrophobic residues is consistent with the primarily electrostatic nature of actin-Tm binding.…”
Section: Discussionsupporting
confidence: 88%
“…Subsequent biochemical and biophysical studies defined features of the Tm molecule that are important for actin binding and regulation, including the molecular ends, an uninterrupted heptad repeat, regions of local instability at the coiled coil interface characterized by the presence of small nonpolar residues such as Ala, and a sequence pattern on the surface of the coiled coil that was proposed as a recognition site for actin binding (8 -11). Previous studies have also shown that individual periodic repeats of Tm contribute in different ways to actin binding and regulatory function (11)(12)(13)(14)(15). Atomic models based on electron microscopy (EM) reconstructions, threedimensional fluorescence resonance energy transfer (FRET) analysis and computational modeling of actin-Tm have revealed the positions of Tm on the actin filament in the absence and presence of troponin Ϯ Ca 2ϩ , and myosin S1 (16 -19).…”
Section: Tropomyosin (Tm)mentioning
confidence: 99%
“…19 Previous studies have also shown that individual periodic repeats of Tm are quasi-equivalent and contribute in different ways to actin binding and regulatory function. [20][21][22][23][24] Crystal structures of Tm fragments have shown that the coiled coil structure is not uniform along the length of the molecule and there are variations in the interhelical distance and pitch of the coiled coil as well as bends and staggers in the molecule. [25][26][27] A solution structure of the striated muscle Tm overlap complex gave some insight into how the proposed periodic actin binding sites on Tm relate to the actin monomers in the actin filament.…”
Section: Actin Binding and Actomyosin Regulation By Tropomyosinmentioning
confidence: 99%